Lesbian Mothers Accounts of Gender in American Culture - Lewin, Ellen (Cornell University Press, 1993)
Within a society that long considered "lesbian motherhood" a contradiction in terms, what were the experiences of lesbian mothers at the end of the twentieth century? In this illuminating book, lesbian mothers tell their stories of how they became mothers; how they see their relationships with their children, relatives, lovers, and friends and with their children's fathers and sperm donors; how they manage child-care arrangements and financial difficulties; and how they deal with threats to custody. Ellen Lewin's unprecedented research on lesbian mothers in the San Francisco area captured a vivid portrait of the moment before gay and lesbian parenting moved into the mainstream of U.S. culture. Drawing on interviews with 135 women, Lewin provided her readers with a new understanding of the attitudes of individual women, the choices they made, and the texture of their daily lives. book_bio_notes: Ellen Lewin is a cultural anthropologist who holds a joint appointment in the departments of Gender, Women's & Sexuality Studies and Anthropology at The University of Iowa. She is the author of Recognizing Ourselves: Ceremonies of Lesbian and Gay Commitment and Gay Fatherhood: Narratives of Family and Citizenship in America.